INFLUENCE OF THE SAGITTAL LUMBAR PARAMETERS ON THE STRESS-STRAIN STATE OF THE SPINAL MOTOR SEGMENTS AT TRANSPEDICULAR FIXATION - Barkov, Barkov; Veretelnik, Oleg; Tkachuk, Mykola; Tkachuk, Mykola А.; Veretelnik, Victor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To study the stress-strain state of the elements of the human lumbar spine when we use the transpedicular system, taking into account different angular values of segmental and total lumbar lordosis. Methods. For computer modeling of the stress-strain state of the elements of the human lumbar spine after mono- and polysegmental fixation, the Workbench product was used, and for the construction of parametric three-dimensional geometric models — the SolidWorks computer-aided design system was used. 4 groups of decisions were studied, which differed in angular values of segmental and total lumbar lordosis. In each group, 11 models were analyzed that describe the lumbar segments after mono- and polysegmental fixation in various configurations of the sagittal alignment of the lumbar spine. Results. It was found that the maximum stress on the cortical bone is concentrated on the base of the LV in case of the «pathological» intervertebral disc LV–S in the group of patients with hyperlordosis. At polysegmental fixation of the LI – S, there is a redistribution of stress on the cortical bone of all vertebrae, the maximum values of which is present in the bodies of the LV and S vertebrae. And only in the group with hypolordosis this stress is minimal. The maximum stress was always on the overlying intervertebral disc during transpedicular fixation. Significant increasing of cartilage stress in the facet joints of the LIV–LV segment was recorded during fixation of the LV–S segment in case of hyperlordosis. The maximum stress on the rods was identified in the group of patients with hyperlordosis and polysegmental fixation of the LI –S, on screws — on LV, LIV, LIII vertebrae during fixation in all groups, except for hypolordosis. Conclusions. Increasing in angular values (hyperlordosis), which describe segmental and total lumbar lordosis, leads to the stress elevation in the fixing elements and structures of the spinal motor segments, and, conversely, a decreasing in angular values (hypolordosis) causes the stress falling.